A comparative study of the Malaysian financial and economic policies in Islamic perspective, 1970-85 - Choudhury, Masud Alam; Abdul Malik, Uzir (Universiti Utara Malaysia, 1988)
The estimated equations of Islamic general economic equilibrium for the Malaysian economy, for the period 1970-85, will now be examined in view of the actual changes that have taken place in Malaysia for the stated period. We shall then study the related policy issues and the potential for policy development in Islamic perspectives. The general forms of the estimated equations were found to reinforce the theoretical structure of the Islamic macro-economic system developed in an earlier work. By the same token the Keynesian element of the Islamic macroeconomic system were found to hold in our estimated model system. However, a critical examination on the stability of the IIS and ILM curves showed low levels of reliability on the estimated slopes of these curves expressed in the log-linear forms. The unstable nature of the slopes of IIS-equation was also reflected in the variable interrelationships within the expenditure sector equation; that is, as shown among income, investment and profit rate variables in their log-linear forms. Likewise, in the case of ILM-equation, the monetary sector equilibrium was found to be unstable. While such cases of instability, shown by the possible ambiguity of the slopes of 11s-ILM-equations, are consistent both with the Keynesian general equilibrium system and the Islamic macro-economic equilibrium, they must be interpreted now in relation to the actual economic changes in the Malaysian economy for the period 1970-85.